2009
DOI: 10.1021/la901128k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Oxides on the Colloidal Stability of Multi-Walled Carbon Nanotubes: A Structure−Property Relationship

Abstract: As with all nanomaterials, a large fraction of the atoms in carbon nanotubes (CNTs) reside at or near the surface. Consequently, surface chemistry will play a crucial role in determining the fate and transport of CNTs in aquatic environments. Frequently, oxygen-containing functional groups (surface oxides) are deliberately grafted into the CNT surface to promote colloidal stability. To study the influence that both the oxygen concentration and the oxygen functional-group distribution have on the colloidal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
209
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(235 citation statements)
references
References 73 publications
21
209
1
Order By: Relevance
“…Toxicity attributed to C 60 in those studies is instead more likely linked to THF decomposition products, as demonstrated in a study with zebrafish [71] and further confirmed in subsequent research [72]. Results showing that (THF-nC 60 ) does not generate oxidative injury (or any other toxic effects) when THF and THF decomposition products are removed [72] resulted in a convincing rejection of the hypothesis that C 60 was responsible for the toxicity reported in studies that have used THF-nC 60 . Despite this evidence, numerous articles continue to cite studies that have used THF-nC 60 to indicate toxicity of C 60 (see, for example, Kahru and Dubourguier [73]).…”
Section: Cnp Dispersion Methods For Ecotoxicity Testssupporting
confidence: 52%
See 4 more Smart Citations
“…Toxicity attributed to C 60 in those studies is instead more likely linked to THF decomposition products, as demonstrated in a study with zebrafish [71] and further confirmed in subsequent research [72]. Results showing that (THF-nC 60 ) does not generate oxidative injury (or any other toxic effects) when THF and THF decomposition products are removed [72] resulted in a convincing rejection of the hypothesis that C 60 was responsible for the toxicity reported in studies that have used THF-nC 60 . Despite this evidence, numerous articles continue to cite studies that have used THF-nC 60 to indicate toxicity of C 60 (see, for example, Kahru and Dubourguier [73]).…”
Section: Cnp Dispersion Methods For Ecotoxicity Testssupporting
confidence: 52%
“…Perhaps the principal example of an artifact that impacted the interpretation of nanoecotoxicology results was with tetrahydrofuran-dispersed fullerenes (THF-nC 60 ). The hypothesis that THF-nC 60 can induce oxidative injury in aquatic organisms was supported in early studies [22,70] but has subsequently been refuted as techniques for investigating toxicity of C 60 have been refined.…”
Section: Cnp Dispersion Methods For Ecotoxicity Testsmentioning
confidence: 99%
See 3 more Smart Citations